Cephalometrıc Set-Up - Erhan Özdiler (Galenos Yayinevi, 1991)
In treatment of dentofacial displazies orthodontist and surgent cooperation is becaming a routine procedure. The aim of this paper is to point out the principles of the pre-surgery radiographic set-up for the adult progeni cases.